Acetyl-CoA Metabolism and Histone Acetylation in the Regulation of Aging and Lifespan - Patrick C. Bradshaw (MDPI AG, 2021)
Acetyl-CoA is a metabolite at the crossroads of central metabolism and the substrate of histone acetyltransferases regulating gene expression. In many tissues fasting or lifespan extending calorie restriction (CR) decreases glucose-derived metabolic flux through ATP-citrate lyase (ACLY) to reduce cytoplasmic acetyl-CoA levels to decrease activity of the p300 histone acetyltransferase (HAT) stimulating pro-longevity autophagy. Because of this, compounds that decrease cytoplasmic acetyl-CoA have been described as CR mimetics. But few authors have highlighted the potential longevity promoting roles of nuclear acetyl-CoA. For example, increasing nuclear acetyl-CoA levels increases histone acetylation and administration of class I histone deacetylase (HDAC) inhibitors increases longevity through increased histone acetylation. Therefore, increased nuclear acetyl-CoA likely plays an important role in promoting longevity. Although cytoplasmic acetyl-CoA synthetase 2 (ACSS2) promotes aging by decreasing autophagy in some peripheral tissues, increased glial AMPK activity or neuronal differentiation can stimulate ACSS2 nuclear translocation and chromatin association. ACSS2 nuclear translocation can result in increased activity of CREB binding protein (CBP), p300/CBP-associated factor (PCAF), and other HATs to increase histone acetylation on the promoter of neuroprotective genes including transcription factor EB (TFEB) target genes resulting in increased lysosomal biogenesis and autophagy. Much of what is known regarding acetyl-CoA metabolism and aging has come from pioneering studies with yeast, fruit flies, and nematodes. These studies have identified evolutionary conserved roles for histone acetylation in promoting longevity. Future studies should focus on the role of nuclear acetyl-CoA and histone acetylation in the control of hypothalamic inflammation, an important driver of organismal aging.